2012
DOI: 10.3389/fonc.2012.00011
|View full text |Cite
|
Sign up to set email alerts
|

Current Status and Future Perspectives on the Etiology of Esophageal Adenocarcinoma

Abstract: Esophageal adenocarcinoma is the most common type of esophageal cancer in most Western countries and is an important contributor to overall cancer mortality. Most cases of esophageal adenocarcinoma are believed to arise from Barrett’s esophagus. Esophageal adenocarcinoma occurs more frequently in white men over 50 years old, as well as in people with frequent symptoms of gastroesophageal reflux, in smokers and in people who are obese. Higher consumption of fruit and vegetables, use of non-steroidal anti-inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 114 publications
0
24
0
Order By: Relevance
“…74,75 In a Swedish nationwide case-control study, GERD and obesity were identified as strong and independent risk factors for EAC. 76 Barrett's esophagus Long standing GERD is strongly associated with development of Barrett's esophagus; the transformation of esophageal mucosal lining from normal stratified squamous to "intestine like" columnar epithelium with goblet cells (intestinal metaplasia).…”
Section: Reflux Disease Barrett's Esophagus (Be) and Esophageal Adenmentioning
confidence: 99%
“…74,75 In a Swedish nationwide case-control study, GERD and obesity were identified as strong and independent risk factors for EAC. 76 Barrett's esophagus Long standing GERD is strongly associated with development of Barrett's esophagus; the transformation of esophageal mucosal lining from normal stratified squamous to "intestine like" columnar epithelium with goblet cells (intestinal metaplasia).…”
Section: Reflux Disease Barrett's Esophagus (Be) and Esophageal Adenmentioning
confidence: 99%
“…According to our results and the previous reports, short-term infusional 5-FU and cisplatin combination in previously untreated locally advanced or metastatic esophageal squamous cell cancer were seem to be similar with continuous infusional 5-FU in terms of median OS and PFS. However, grade 3-4 toxicity rates were more frequent than infusional 5-FU except for grade [3][4] Despite the consideration of infusional chemotherapy as standard regimen for the treatment of esopahegeal cancer, there is a main problem with these regimens. This is the neccesity for a central venous catheter and ambulatory infusion pump.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer of the esophagus typically occurs in one of two forms; upper two-thirds is a squamous cell carcinoma (SCC) and lower one-third is an adenocarcinoma.It is assumed that there are complete differences between esophageal adenocarcinomas and squamous cell cancer, such as the treatment protocol and prognosis. (1,2,3) Cytotoxic chemotherapy is the most effective treatment modality for esophageal cancer patients with metastatic disease. (4) Grunberger et al have showed that palliative chemotherapy can prolong the survival of metastatic esophageal cancer patients, relieve their symptoms and improve their quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…19 Both acid and bile have been implicated as injurious and potentially mutagenic through direct DNA damage and activation of inflammatory pathways such as NF-kappa beta, which have downstream effects on cell proliferation. 20 Although reflux is very common, only a small proportion of people will go on to develop metaplasia, and it is likely that host genetic influences are important in this.…”
Section: Molecular Pathways Of Progression In Bomentioning
confidence: 99%